2016
DOI: 10.1155/2016/1536047
|View full text |Cite
|
Sign up to set email alerts
|

FFAR4 (GPR120) Signaling Is Not Required for Anti-Inflammatory and Insulin-Sensitizing Effects of Omega-3 Fatty Acids

Abstract: Free fatty acid receptor-4 (FFAR4), also known as GPR120, has been reported to mediate the beneficial effects of omega-3 polyunsaturated fatty acids (ω3-PUFAs) by inducing an anti-inflammatory immune response. Thus, activation of FFAR4 has been reported to ameliorate chronic low-grade inflammation and insulin resistance accompanying obesity. However, conflicting reports on the role of FFAR4 in mediating the effects of ω3-PUFAs are emerging, suggesting that FFAR4 may not be the sole effector. Hence analyses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 58 publications
(92 reference statements)
0
36
1
Order By: Relevance
“…Notably, the in vivo significance of GPR120/FFA4 to suppress chronic low‐grade inflammation also has lately been contended. While GPR120/FFA4 activation by ω3‐PUFAs was initially reported to be critical to reduce high‐fat diet‐induced adipose tissue inflammation, more recent studies found GPR120/FFA4 to be dispensable for the therapeutic effects of ω3‐PUFAs in mouse models of both high‐fat diet‐induced adipose tissue inflammation, and of atherosclerosis . The reason for these discrepant findings is unknown and numerous explanations are conceivable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the in vivo significance of GPR120/FFA4 to suppress chronic low‐grade inflammation also has lately been contended. While GPR120/FFA4 activation by ω3‐PUFAs was initially reported to be critical to reduce high‐fat diet‐induced adipose tissue inflammation, more recent studies found GPR120/FFA4 to be dispensable for the therapeutic effects of ω3‐PUFAs in mouse models of both high‐fat diet‐induced adipose tissue inflammation, and of atherosclerosis . The reason for these discrepant findings is unknown and numerous explanations are conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…While GPR120/FFA4 activation by ω3-PUFAs was initially reported to be critical to reduce high-fat diet-induced adipose tissue inflammation, 14 more recent studies found GPR120/FFA4 to be dispensable for the therapeutic effects of ω3-PUFAs in mouse models of both high-fat diet-induced adipose tissue inflammation, and of atherosclerosis. 35,36 The reason for these discrepant findings is unknown and numerous explanations are conceivable. Inflammation is a most complex process and ω3-PUFAs can exert diverse pharmacological actions independent of GPR120/FFA4.…”
Section: Discussionmentioning
confidence: 99%
“…FFAs by inducing an anti-inflammatory response and regulating insulin metabolism is discussed by Paerregaard et al (124). In their latest study, and contradicting most existing literature, they proposed that GPR120 is dispensable for the beneficial effects that ω-3 FFAs display in obese mice.…”
Section: Gpr120 (Ffar4)mentioning
confidence: 98%
“…Dietary omega‐3 fatty acids have been demonstrated to reduce the inflammation derived from adipose tissues as summarized in Table . In the adipose tissue, omega‐3 fatty acids reduce the mRNA levels of pro‐inflammatory adipokines such as MCP‐1 , IL‐6 , and TNF‐α in high‐fat‐induced obese mice and MCP‐1 in obese humans . In addition, supplementation of omega‐3 fatty acids reduces systemic inflammation, resulting in a decrease in plasma MCP‐1 levels in insulin‐resistant obese individuals and plasma CRP levels in obese pregnant women …”
Section: Preventive Effects Of Omega‐3 Fatty Acids In Metabolic Syndrmentioning
confidence: 99%
“…GPR120 was suggested to mediate the anti‐inflammatory effects (i.e., suppression of macrophage pro‐inflammatory cytokine secretion) of omega‐3 fatty acids . However, this was contradicted by the results of other studies and the receptors that bind omega‐3 fatty acids remain unclear.…”
Section: Preventive Effects Of Omega‐3 Fatty Acids In Metabolic Syndrmentioning
confidence: 99%